Fifth Order Improved Runge-Kutta Method for Random Initial Value Problems - Omar, Almbrok; Ahmed, Iman (Journal of Pure & Applied Sciences, 2018)
When the initial conditions of differential equations are random in nature, the mathematical description of the solution in terms of initial conditions must be modified by considering the initial conditions as random variables having a particular statistical distribution. In this paper, the fifth order improved Runge-Kutta method (IRK5) is modified for the approximation of the solution of the random initial value problems (RIVPs). Numerical simulation was carried out. Some properties of the random behavior and the effect of the randomness were investigated.